Interviewing Elites, Experts and the Powerful in Criminology - Petintseva, Olga (Springer eBooks Law and Criminology, 2020)
1. Introduction -- 2. Interviewing ‘The Powerful’ In Crime And Crime Control -- 3. Interview Models And Researcher’s Self-Positioning -- 4. Their Reign, Their Game? Accessing The Powerful -- 5. Prepare, Prepare, Prepare -- 6. Conducting The Interview -- 7. Making Sense Of The Data